A educação libertadora em direitos humanos e a formação dialógica de professores de ciências: um olhar para as produções científicas internacionais - Ponte, Laís de (Universidade Federal de São Carlos, 2026)
Human Rights are fundamental constituents of the global society and the democratic processes. Based on this assumption, it is possible to integrate them into science teaching in order to promote a culture of human rights, as well as foster collective empowerment aimed at social transformation. Given these facts, the present study has the purpose of mapping the academic productions on the theme. The question that guided this study was: what perspectives have international research studies highlighted regarding science teacher education within the framework of human rights education, and how do these studies point toward teaching practices committed to social transformation? A bibliographic review was adopted as the research method, focusing on two international databases: ERIC and SCOPUS. The research identified 26 articles published over the last ten years which connect science education and human rights. Furthermore, the analysis focused on articles that prioritize science teacher training. The results indicate a strong tendency toward critical rationality in teacher training, emphasizing teachers as sociocultural agents and committed to social transformation. It is expected that this study will contribute to the academic discussion of the topic in a dialogical perspective and offer future possibilities for science education and teacher training.
Liberating education in human rights and the dialogical training of science teachers: a look at international scientific productions
La educación libertadora en derechos humanos y la formación dialógica de profesores de ciencias: una mirada a las producciones científicas internacionales
Keywords: Educação em ciências; Ensino de ciências; Formação de professores; Transformação social; Empoderamento; Science education; Science teaching; Teacher training; Social transformation; Empowerment; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade